Sino-Soviet Conflict, 1956-1961 - Zagoria, Donald S. (Book collections on Project MUSE., 2015)
What happens if the two most powerful partners in the Communist world cannot agree on basic issues of principle and policy? Donald S. Zagoria, who was from 1951 to 1961 an analyst of Communist Bloc politics for the U.S. Government, traces the development of serious conflict between the U.S.S.R. and China from the 20th Party Congress in 1956 to the 22nd Party Congress in late 1961. This conflict has enveloped three major areas-global strategy, domestic policy, and intra-Bloc relations-and has plagued the relations between Khrushchev and Mao Tse-tung and affected their differing attitudes toward de-Stalinization, the communes, Yugoslavia, Taiwan, and the developing African and Asian nations. In studying these differing policies, Mr. Zagoria makes extensive use of the published statements of the Chinese and Russian Communists; his analysis of this literature is in itself an important contribution to all future evaluations of Communist intentions. Originally published in 1962. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.